2016
DOI: 10.1039/c6ra19902j
|View full text |Cite
|
Sign up to set email alerts
|

Copper(ii) complexes with aromatic nitrogen-containing heterocycles as effective inhibitors of quorum sensing activity in Pseudomonas aeruginosa

Abstract: Copper(ii) complexes with aromatic nitrogen-containing heterocycles are a new class of quorum sensing inhibitors that attenuate virulence without a pronounced effect on the bacterial growth, thus offering a lower risk for resistance development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 93 publications
3
30
0
Order By: Relevance
“…The high activity was detected for the compound 1 against bacterium of P. aeruginosa PAO1 with the MIC value 0.5 m m (302 μg/ml). Considering the MIC values for other transition metal complexes towards P. aeruginosa PAO1 (Ag(I) complexes – MIC=2–15 μg/ml, Au(III) complexes – MIC=10−30 μg/ml, Cu(II) complexes – MIC=500–1000 μg/ml), it can be concluded that the tested ruthenium complexes show moderate bacteriostatic activity. In comparison to tested antibiotic, the studied ruthenium compounds exhibit much lower bacteriostatic effects on the bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high activity was detected for the compound 1 against bacterium of P. aeruginosa PAO1 with the MIC value 0.5 m m (302 μg/ml). Considering the MIC values for other transition metal complexes towards P. aeruginosa PAO1 (Ag(I) complexes – MIC=2–15 μg/ml, Au(III) complexes – MIC=10−30 μg/ml, Cu(II) complexes – MIC=500–1000 μg/ml), it can be concluded that the tested ruthenium complexes show moderate bacteriostatic activity. In comparison to tested antibiotic, the studied ruthenium compounds exhibit much lower bacteriostatic effects on the bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Biologically active metal complexes have gained special significance due to the need for the prevention of resistance of bacterial strains. Recently, several Cu(II), Ga(III), Zn(II), Mn(II), Ag(I), Au(III) and Ru(II) complexes with bioactive ligands have been tested as potential antibiofilm and antimicrobial agents . Among above mentioned metal complexes, ruthenium compounds are promising for medicinal and biotechnological applications as they present unique properties: (i) multiple oxidation states (II, III and IV), which are accessible in physiological conditions; (ii) favorable ligand‐exchange kinetics; (iii) multiple cytotoxic routes involving the competing processes of extracellular protein binding (active transport), due to the ability to mimic iron and cellular uptake (passive diffusion); (iv) different molecular pathways involving the concurrent intercalation and covalent binding with DNA and binding to extracellular sites inducing conformational modifications; (v) numerous synthetic opportunities for modifying the biological activity which depends on both the oxidation state of the metal center and the associated ligands surrounding it.…”
Section: Introductionmentioning
confidence: 99%
“…Copper(II) complexes with 4,7-phenanthroline, [Cu(NO 3 ) 2 (4,7-Hphen) 2 ](NO 3 ) 2 (1) and [Cu(CF 3 SO 3 )(4,7-phen) 2 (H 2 O) 2 ]CF 3 SO 3 (2) were synthesized according to the modified procedure for the preparation of copper(II) complexes with aromatic N-heterocycles [22]. The solution of 0.5 mmol of CuX 2 salt (120.8 mg of Cu(NO 3 ) 2 -Á3H 2 O for 1 and 180.8 mg of Cu(CF 3 SO 3 ) 2 for 2) in 5.0 mL of ethanol was added slowly under stirring to the solution containing an equimolar amount of 4,7-phen (90.1 mg) in 5.0 mL of ethanol.…”
Section: Synthesis Of Copper(ii) Complexes 1 Andmentioning
confidence: 99%
“…Very recently, five copper(II) complexes with aromatic nitrogen-containing heterocycles (N-heterocycles), e.g. pyrimidine, pyrazine, quinazoline and phthalazine, were synthesized and evaluated for their activity against three clinically important pathogens, namely Pseudomonas aeruginosa, Staphylococcus aureus and Candida albicans [22]. The obtained results showed that none of the studied copper(II) complexes manifested significant growth inhibiting activity against the investigated strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation